A experiência dos alunos idosos no PROEJA e PROEJA FIC (Programa Nacional de Integração da Educação Profissional com a Educação Básica na Modalidade de Educação de Jovens e Adultos do Nível Fundamental e Médio) do IFSP - Silva, Cibele Sales da (2018)
This research has the objective of analyzing the effects of PROEJA and PROEJA FIC of the Federal Institute of Education Science and Technology of São Paulo (IFSP), in the daily life of the elderly students, as well as the reasons to return to study, their expectations and the way of sociability that is constituted in this institutional space. PROEJA and PROEJA FIC arise as a proposal to integrate Vocational Education for Youth and Adult Education, through Decree n. 5,840 / 2006. It presents itself as an alternative for the elderly segment that seeks professionalism and new forms of learning. Through the bibliographic study, the present research presents the IFSP, its history and expansion, as well as the social policies for the elderly, actions oriented to the segment from the 70's, the elderly and educational exclusion, which brings the reflection illiteracy and legislation. Youth and adult education, vocational education and education are contextualized in order to understand the evolution of these educational policies at the national level. The empirical research, of a qualitative nature, carried through interviews, brings the report of these students, evidencing the breakage of stigmatized old age, facing a new way of aging: the elderly student with expectations, dreams and life projects